Spatial variation in household-level risk to natural hazards across the coast of Bangladesh. Issue 1 (1st January 2021) - Quader, Mohammad Abdul; Khan, Amanat Ullah; Kervyn, Matthieu
Abstract: People's vulnerability, exposure and capacity are key components of a risk assessment. Index-based methodologies have proved useful to document spatial variation in risk-controlling factors. The objective of this study is to propose a methodology to derive quantitative indicators of household vulnerability, exposure and capacity to assess household's risk and its spatial variation. The method is applied to six unions of the coastal region of Bangladesh, including three offshore islands. Field data are collected by questionnaire survey of 609 households and 6 focus group discussions. Using conventional data conversion and aggregation methods and principle component analysis (PCA), the variables are summarized into a small set of dimensions to derive vulnerability and capacity scores. Result shows that households of islands are generally more vulnerable to natural hazards than nearby onshore unions. Unions of the central coast of Bangladesh are characterized by households with higher vulnerability and lower capacities than two other parts. The fatality rate of cyclone SIDR at village level is used to validate the spatial variation of household risk for one surveyed union. The proposed methodology and produced maps could support national to local government bodies in assessing household risk and identifying locations where to implement specific risk reduction measures.